Quantitation of IgG kappa and IgG lambda in the cerebrospinal fluid by sandwich ELISA method - Zeman, David; Kušnierová, Pavlína; Bojková, Jana; Všianský, František; Zapletalová, Olga (Journal of immunoassay & immunochemistry, 2017)
IgG kappa and IgG lambda concentrations were quantified in 96 paired CSF and sera using Hevylite™ antibodies in an in-house developed sandwich ELISA method. In 56 of these samples, the results were compared with a qualitative isoelectric focusing/affinity-mediated immunoblotting assay for oligoclonal IgG kappa and IgG lambda. Normal IgG kappa/lambda ratio in the CSF was the same as in serum. In 19/33 patients with intrathecal oligoclonal IgG synthesis, skewed IgG kappa/lambda ratio was observed (increased in 16 and decreased in 3 cases). The analysis of light chain composition of intrathecally synthesised immunoglobulins could contribute to our understanding of intrathecal humoral immune response, although its diagnostic utility is limited.
Keywords: Immunoglobulin G; Enzyme-Linked Immunosorbent Assay; Immunoglobulin kappa-Chains; Immunoglobulin lambda-Chains; imunoglobuliny - kappa-řetězce; lidé; ELISA; imunoglobulin G; imunoglobuliny - lambda-řetězce; Humans